2020
DOI: 10.1073/pnas.2006209117
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Z nucleotides as an ancient signal for two-component system activation in bacteria

Abstract: Two-component systems (TCSs) in bacteria are molecular circuits that allow the perception of and response to diverse stimuli. These signaling circuits rely on phosphoryl-group transfers between transmitter and receiver domains of sensor kinase and response regulator proteins, and regulate several cellular processes in response to internal or external cues. Phosphorylation, and thereby activation, of response regulators has been demonstrated to occur by their cognate histidine kinases but also by low molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 67 publications
1
7
0
Order By: Relevance
“…Also, addition of acetate, but not formate, resulted in the activation of reporter expression in the ΔbarA mutant strain (Fig. 1C), due to acetyl-P−dependent UvrY phosphorylation, in agreement with previous reports (15,34). On the other hand, no activation of csrB-lacZ expression was observed in the strains expressing the BarA Δ1-197 or the BarA PDArcB proteins, indicating that these BarA variants fail to respond to acetate and formate, but retain their phosphatase activity, and are therefore functional proteins that remain locked in their phosphatase state.…”
Section: The Periplasmic Region Of Bara Is Required For Activation Of Its Kinase Activitysupporting
confidence: 93%
“…Also, addition of acetate, but not formate, resulted in the activation of reporter expression in the ΔbarA mutant strain (Fig. 1C), due to acetyl-P−dependent UvrY phosphorylation, in agreement with previous reports (15,34). On the other hand, no activation of csrB-lacZ expression was observed in the strains expressing the BarA Δ1-197 or the BarA PDArcB proteins, indicating that these BarA variants fail to respond to acetate and formate, but retain their phosphatase activity, and are therefore functional proteins that remain locked in their phosphatase state.…”
Section: The Periplasmic Region Of Bara Is Required For Activation Of Its Kinase Activitysupporting
confidence: 93%
“…Although FimZ also stimulated constant cell elongation in hisH‐ and purC‐ deficient strains (e and f in Figure 5a), as the defective purA gene suppressed cell elongation (g in Figure 5a). Addition of AMP, which prevents ZMP/ZTP accumulation in purA null mutants (Vázquez‐Ciros et al, 2020; Watanabe et al, 2011), recovered cell elongation suppression in purA null mutants (h in Figure 5a). The D56A mutant also recovered cell elongation suppression in purA null mutants (i in Figure 5a).…”
Section: Resultsmentioning
confidence: 92%
“…The reporter assay showed that the sfmA promoter was significantly induced in all mutants (Figure S7A). A response regulator is usually phosphorylated by low‐molecular‐weight phosphorylated compounds, acetyl phosphate, and Z‐nucleotides (Vázquez‐Ciros et al, 2020; Wolfe, 2005). The sfmA promoter was induced in cobB, ackA, pta , and yfiQ mutants, similar to that in the parent strain, and purA deficiency slightly enhanced the sfmA promoter activity (Figure S7B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many response regulators can catalyze their own phosphorylation using small molecule phosphodonors (Lukat et al ., 1992; Silversmith et al ., 1997; Vazquez-Ciros et al ., 2020; Wolfe, 2010). Changes in fluorescence intensity of a Trp residue upon phosphorylation at a neighboring residue was used to demonstrate autophosphorylation of the Brucellus abortis NtrX receiver domain with acetyl phosphate (Fernandez et al ., 2015).…”
Section: Resultsmentioning
confidence: 99%